Real life evaluation of the multi-organ effects of Lumacaftor/Ivacaftor on F508del homozygous cystic fibrosis patients - Karin Yaacoby-Bianu; Zeev Schnapp; Ilana Koren; Anat Ilivitzki; Mohamed Khatib; Nadeem Shorbaji; Michal Shteinberg; Galit Livnat (BMC, 2022)
Abstract Background Lumacaftor/Ivacaftor (LUM-IVA), a cystic fibrosis transmembrane conductance regulator (CFTR) protein corrector-potentiator combination, improves lung function and reduces pulmonary exacerbations (PEx) in F508del homozygous CF patients. However, the systemic effects of LUM-IVA outside the respiratory system have not yet been thoroughly investigated. Methods A prospective, real-world, yearlong study was performed on F508del homozygous adult CF patients who commenced treatment with LUM-IVA. Pancreatic function, bone metabolism, fertility status, nutritional and pulmonary factors were evaluated. Results Twelve patients, mean age 28.3 years (18.6-43.9) were recruited. Following 12 months of treatment, no changes were detected in glucose, insulin, c-peptide or BMI values. A significant relative decrease in mean alkaline-phosphatase levels (122.8 U/L vs 89.4, p = 0.002) and a trend toward an increase in calcium levels (9.5 vs 9.9 mg/dL, p = 0.074) were observed. A non-significant improvement in mean DEXA spine t-score after a year of treatment (-2.1 vs -1.6, n = 4, p = 0.11) was detected. Sweat chloride concentrations decreased significantly (-21.4 mEq/L; p = 0.003). Pulmonary outcome revealed improvement in spirometry values during the first three months (FEV1 by 5.7% p = 0.009, FEF25-75 by 4.3% p = 0.001) with no change in chest CT Bhalla score and CFQR after one year. There was also a significant decrease in parenteral antibiotic events (17 vs 8, p = 0.039) with shift from IV to oral antibiotics for PEx treatment. Conclusions After one year of treatment, stabilization was observed in the pancreatic indices, nutritional status, structure and function of the lungs, with a beneficial effect on bone mineral metabolism and CFTR function. Additional studies should investigate the effect of CFTR modulators on extra-pulmonary manifestations.